(untitled) - Vujicic, Nick; (1982-...) (U.S.A, 2014)
In (3z(BLove Without Limits(3y (BNick and Kanae tell how they improbably found each other, fell in love, and then fought to overcome skepticism from others about their relationship. Filled with practical insights that will benefit any couple, this inspiring book describes a godly courtship and the early years of the Vujicics$1 (Bmarriage and parenting journey.s
Keywords: Marriage -- Religious aspects -- Christianity